The Use of Coached Clients in Summer Practicum Programs - Shymko, Dolores L.; Weiser, John C. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper discussed the use of coached clients in summer counselor education programs. The coached clients were utilized to assist in developing basic communication skills, in learning goal-setting and case handling procedures, and for practicing particular counseling techniques. Some of the benefits in using coached clients in summer practicum pro- grams were discussed. They can be used to give the counselor trainees personal feedback and to help evaluate recorded interviews. The importance of the selection and training of the coached clients was emphasized. Some of the positive and negative reactions of students included in the programs were given, with suggestions for future improvements.